Effect of standardized ginseng extract on erythrocyte 2,3-diphosphoglycerate - Areeya Chongsatientam (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The present study was carried out with humans to determine the effect of 8wk administration of standardized ginseng extract on blood 2,3-diphosphoglycerate levels at rest and during exercise. Sixteen healthy male university students were initially participated and were equally divided into two groups as ginseng (G, n=8) and placebo (P, n=8). Group G and Group P received standardized ginseng extract and placebo capsules, respectively, under double-blind condition for 8 wk. The dose of the ginseng extract was 300mg d(-1). Another subject group, designated as control (C, n=7) and received neither ginseng nor placebo, was added in this study to observe by comparison with group P any physiological effects of placebo. An incremental cycling exercise test for determination of maximal oxygen consumption (VO(,2max)) was performed by individual subjects in each group at the beginning and at the end of the 8-week experimental period. Resting and postexercise hemoglobin (Hb), hematocrit (Hct), reticulocyte count, mean corpuscular hemoglobin concentration (MCHC), 2,3-diphosphoglycerate (2,3-DPG), serum inorganic phosphate (INP), and blood lactate (LAC) were also determined. No significant changes in VO(,2max) from the O-week values was observed in the three subject groups by 8 weeks and no significant difference in VO(,2max) among group were found. LAC was significantly enhanced by exercise in all groups and the changes were similar among the groups. Resting and postexercise values of 2,3-DPG, reticulocyte count, MCHC, and lNP were also not significantly different from those of group P and group C. No significant correlation between VO(,2max) and resting and postexercise 2,3-DPG were observed. This finding indicates that ginseng administration, under the present experimental regimen, had no effect on both resting and exercising erythrocyte 2,3-DPG concentration levels as well as on maximal aerobic power in healthy young males.